PEMETAAN LINTASAN PEMBELAJARAN DAN KEFEKTIFAN MEDIA PEMBELAJARAN DALAM MATERI TURUNAN FUNGSI ALJABAR - Tampubolon, Andreas; Sigalingging, Dame Enjelina; Harahap, Dwita Meliani; Silitonga, Natalia Susi Susanti Silitonga; -, Kairuddin (Program Studi Pendidikan Matematika Institut Pendidikan Tapanuli Selatan, 2025)
This research aims to map learning trajectories and analyze the effectiveness of using learning media in improving students' understanding of material derived from algebraic functions in class XII SMAN 12 Medan. Considering students' difficulties in understanding abstract concepts, this research develops a learning trajectory by involving various learning media, such as PowerPoint presentations, animated videos, manual teaching aids, namely the Derivative Wheel, digital teaching aids, namely GeoGebra, and LKPD as a means of driving student activity. This research focuses on developing realistic and contextual learning methods. This research reveals that the use of a combination of diverse educational media can help students understand the concept of abstract and complex derivatives of algebraic functions, as well as increase student participation in the learning process. This research emphasizes the importance of the Realistic Mathematics Education (RME) approach to creating contextual and relevant learning, as well as providing recommendations for teachers to continue developing innovative learning methods.